Carbon Stock Assessment along Altitudes in Agrisilviculture Systems of Tehri District, Uttarakhand, North Western Himalaya - Case study of Pratapnagar block - Vikrant, K. K.; Chauhan, D. S.; Rizvi, R. H. (Indian Forester, 2020)
Agroforestry represents an integration of agriculture and forestry to increase productivity and sustainability offarming systems and farm income. Agroforestry is a viable alternative to prevent and mitigate climate change. This study therefore aimed to generate data on the carbon stocks ofagrisilviculture systems located in the Tehri district of Uttarakhand. The methodologies used include measurement of trees at diameter breast height (dbh) and sampling of branch, leaf, crops and soil for carbon content determination. Present results showed that carbon accumulation of agroforestry systems goes along with the following order; upper altitude (2000-2800 m) > middle altitude (1200-2000 m) > lower altitude (286-1200 m). Thus Agrisilviculture are not only remunerative to the farmers but also contributing towards tapping of atmospheric CO2 vis-a-vis mitigation of climate change. Policy programs promoting the establishment of agroforestry systems in ideal lands in Tehri district should be considered.